Effect of Web Openings on Flexural Behaviour of Underground Metro Station RC Beams under Static and Cyclic Loading - Ting-jin Liu; Si-wei Chen; Zi-hang Feng; Hong-yuan Liu (Advances in Civil Engineering)
This paper investigates the influence of multiple transverse web openings on the flexural behaviour of underground metro station reinforced concrete (RC) beams. This problem is outlined with an actual underground engineering project, in which the web opening used in the RC beams violates the current specifications. A total of five beams with different numbers of web openings are fabricated and tested under static and cyclic loading conditions, thereby simulating actual operations in unfavourable conditions. The results suggest that the existence of the openings decreases the loadbearing capacity, ductility, stiffness, and energy dissipation ability of the RC beams. Moreover, the results show that the corners of the openings are the weakest parts of the beams. However, additional reinforcements around the openings can partially mitigate the impact of the openings on the loadbearing and seismic performance of the RC beams. The laboratory experiments presented herein not only provide guidelines for the use of RC beams with web openings in actual engineering projects, especially underground projects where RC beams with web openings have seldom been investigated, but also shed light on improving the related design specifications.